Effect of Supplementation of Combination of Prebiotic and Acidifier on Performance of Broiler Chicken - Khemalapure, Sachin; Ramteke, Bhushan; Gadegaonkar, Ganesh; Karambele, Narendra; Jagadale, Suresh (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
This study was undertaken to evaluate the effect of supplementation of prebiotics (Mannanoligosaccharide, MOS) and acidifier combination on the performance of broilers. The feeding trial was conducted on 135-days-old ‘Cobb-400’ broiler chicks for a period of six weeks. The day-old broiler chicks were randomly divided into three equal groups viz. T0, T1 and T2 comprised 45 birds each, further subdivided into three replicates of 15 birds each. Group T0 served as control and received a standard broiler diet. The birds in groups T1 and T2 were fed diets containing prebiotic (MOS) and acidifier combination @ 0.05% and 0.75%, respectively. The birds from group T1 received diet containing a prebiotic (MOS) and acidifier combination @ 0.05% of feed. The birds from group T2 received a diet containing a prebiotic (MOS) and acidifier combination @ 0.075% of the feed. The final live body weight and total weight gain of birds of T1 group was significantly (p <0.01) higher than control and T2 group. The average feed consumption of birds of experimental groups was comparable. The feed conversion ratio was significantly (p <0.05) better than control and T2 group. The average dressing percentage, giblet weight percentage, gut pH, and gut length of birds of T1 group was comparable. The average total viable count (TVC) and total coliform count (TCC) did not vary between experimental groups The group T1 recorded the highest net profit per bird.